2014
DOI: 10.1111/ijac.12329
|View full text |Cite
|
Sign up to set email alerts
|

Curing Behavior and Structure of Magnesium Phosphate Chemically Bonded Ceramics with Different MgO to KH2PO4 Ratios

Abstract: Magnesium phosphate chemically bonded ceramics attracted much attention because of its good biocompatibility. In this work, curing behavior and microstructure of magnesium phosphate chemically bonded ceramics with different MgO to KH 2 PO 4 ratios were investigated. The results showed that the setting time decreased and the maximum temperature during the solidifying process increased as the increase of MgO to KH 2 PO 4 ratio. Phase compositions were different for those samples fabricated with different MgO to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…The hydration process of MPCs is essentially an exothermic reaction of acid-base neutralization. It is believed that the hydration process of MPC can be divided into several steps: (a) MgO dissolves in water and releases Mg 2+ and OH − ; (b) Mg 2+ reacts with water molecules to form a positively charged hydrosol; (c) the hydrosol subsequently forms hydrogen phosphate with hydrogen phosphate ions; (d) the newly generated hydrogen phosphate forms a molecular network in the aqueous solution and then forms a gel [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The hydration process of MPCs is essentially an exothermic reaction of acid-base neutralization. It is believed that the hydration process of MPC can be divided into several steps: (a) MgO dissolves in water and releases Mg 2+ and OH − ; (b) Mg 2+ reacts with water molecules to form a positively charged hydrosol; (c) the hydrosol subsequently forms hydrogen phosphate with hydrogen phosphate ions; (d) the newly generated hydrogen phosphate forms a molecular network in the aqueous solution and then forms a gel [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…MPC is a new and excellent type of repair material, with the characteristics of early high strength [6], good bonding performance [7], wear resistance [8], freeze-thaw cycle stability [9], and good resistance to acid attacks [10,11]. MPC is a cementitious material formed through a chemical reaction between dead-burned MgO and phosphate (KDP) [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials and fibres can also be used as reinforcement to improve the corrosion resistance [9][10][11]. Besides, the curing process, which can determine the microstructure of CBC, is also investigated to improve wear and corrosion properties [3,12,13]. For example, Zhu et al [14] found the porosity of CBC decreased with the addition of ATP leading to a low corrosion current and high corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%